Lights, Camera, Amalee - Williams, Dar (New York : SCHOLASTIC INC., 2006)
"A poignant, funny debut... readers will be charmed by William's eccentric, lovable characters and her sharp observations about the world of both middle-schoolers and adults" "An uplifting story that will grab young readers"
"Un debut conmovedor y divertido ... los lectores estarán encantados con el excéntrico de William, sus adorables personajes y sus agudas observaciones sobre el mundo de los estudiantes de secundaria y adultos" "Una historia edificante que atraerá a los lectores jóvenes"
Keywords: NORTH AMERICAN LITERATURE -- NOVEL; LITERATURA NORTEAMERICANA -- NOVELA